Constitutive criminology: origins, core concepts, and evaluation - Henry, Stuart (Social justice, 2000)
Part of a special issue on criminal justice at the new millennium. The writers discuss the origins and core concepts of constitutive criminology, a theoretical perspective that they formulated in 1988. They describe the origins of the theory and note the variety of sources that it draws upon. They explain the core concepts of the perspective and conclude by offering an evaluation of the theory's contribution to sociology as a whole.